Integrating remote-sensed and historical geodata to assess interactions between rural buildings and agroforestry land - Cillis, Giuseppe; Statuto, Dina; Picuno, Pietro (Journal of Environmental Engineering and Landscape Management, 2021)
The rural built heritage constitutes a unique example, due to architectural and technical issues, which plays a central role in the formation of rural landscape. In this research, interactions between rural buildings and the surrounding land have been examined. Two case studies exemplifying some of typical dynamics of some internal mountain areas of Mediterranean region have been considered. These areas are located in Basilicata Region (Southern Italy) and suffer from land and rural buildings heritage abandonment, as well as from the concurrent disappearance of agroforestry systems with high ecological value. A multi-chronological geo-database incorporating different land cover datasets over a period of 62 years (1955–1988–2008–2017) has been implemented into a GIS to assess relationships between some rural buildings and the surrounding land have been then assessed. This has been achieved by integrating different types of remote-sensed geodata: historical aerial photos, digital orthophotos and satellite images. The analyses carried out have shown that the intensity of land abandonment can also be related to the type of rural building and prevalent agricultural activity. Moreover, thanks to this methodology, it has been possible to produce several spatial information useful to support public decisionmakers at different level.